HCN2-associated neurodevelopmental disorders: data from patients and xenopus cell models - Houdayer, Clara; Phillips, A. Marie; Chabbert, Marie; Bourreau, Jennifer; Maroofian, Reza; Houlden, Henry; Richards, Kay; Saadi, Nebal Waill; Dad'ová, Eliška; Van Bogaert, Patrick; Rupin, Mailys; Keren, Boris; et al. (Annals of neurology, 2025)
Objective We aimed to characterize the phenotypic spectrum and functional consequences associated with variants in HCN2, encoding for the hyperpolarization-activated cyclic nucleotide (HCN) gated channel 2. Methods GeneMatcher facilitated the recruitment of 21 individuals with HCN2 variants from 15 unrelated families, carrying HCN2 variants. In vitro functional studies were performed by electrophysiology with Xenopus laevis oocytes and membrane trafficking was investigated in HEK cells by confocal imaging. Structural 3D-analysis of the HCN2 variants was performed. Results The phenotypic spectrum included developmental delay/intellectual disability (DD/ID, 17/21), epilepsy (10/21), language disorders (16/21), movement disorders (12/21), and axial hypotonia (10/21). Thirteen pathogenic variants (12 new and 1 already described) were identified: 11 missense (8 monoallelic and 3 biallelic), 1 recurrent inframe deletion (monoallelic), and 1 frameshift (biallelic). Functional analysis of p.(Arg324His) variant showed a strong increase of HCN2 conductance, whereas p.(Ala363Val) and p.(Met374Leu) exhibited dominant negative effects. The p.(Leu377His), p.(Pro493Leu), and p.(Gly587Asp) variants rendered HCN2 electrophysiologically silent and impaired membrane trafficking. Structural 3D-analysis revealed that, except for p.(Arg324His), all variants altered HCN2 stability. Interpretation Our findings broadened the HCN2 disease clinical spectrum to include DD/ID with or without epilepsy. Functional analysis in cellular models reveal that pathogenic HCN2 variants can cause either loss-of-function or gain-of-function, providing critical information for the development of targeted therapies for HCN2-related disorders. ANN NEUROL 2025;98:573-589
Gesehen am 05.11.2025